Functional, histological and molecular characteristics of human exstrophy detrusor. Issue 2 (April 2019) - Johal, N.S.; Arthurs, C.; Cuckow, P.; Cao, K.; Wood, D.N.; Ahmed, A.; Fry, C.H.
Summary: Introduction: Bladder exstrophy is a congenital anomaly involving foetal exposure and protrusion of the open bladder through an incomplete lower abdominal wall. Techniques to surgically correct exstrophy after birth have greatly improved, but it still presents a major challenge to achieve continence and a good quality of life for patients and their families as the pathophysiology of bladder dysfunction is unknown. Objectives: A multimodal approach was used to characterise the histological and biomechanical properties of exstrophy detrusor. These were correlated with myocyte responses to agonists and an evaluation of developmental signalling pathways to evaluate the cause of bladder dysfunction in exstrophy. Study design: Detrusor muscle specimens were obtained during corrective surgery from four exstrophy groups: neonatal (1–3 days, n  = 8), younger children (7 months–5 years, n  = 13) and older children (8–14 years, n  = 11) undergoing secondary procedures and cloacal exstrophy (16 days–9 years, n  = 9); control specimens were obtained from children (3 months–9 years, n  = 14) undergoing surgery for other pathologies but with normal bladder function. Five lines of experiments were undertaken: measurement of connective tissue to detrusor muscle ratio, contractile responses to electrical and agonist stimulation; in vitro biomechanical stiffness, intracellular Ca 2+ responses to contractile agonists and immunohistochemistry for proteins (MMP-7, cyclinD1, β-catenin and c-myc ) involved in fibrosis generation. Exstrophy data were compared with those from the control group. Results: Exstrophy tissue demonstrated reduced smooth muscle compared with connective tissue, reduced contractile responses and greater mechanical stiffness. However, intracellular Ca 2+ responses to agonists were maintained. These changes were greatest in neonatal and cloacal exstrophy samples and least in those from older paediatric bladders. Immunolabelled MMP-7, β-catenin and c-myc were reduced in exstrophy samples. Discussion: These results highlight the reality that newborns with exstrophy have significantly reduced compliance and bladder underactivity, which may persist or return to normal values with surgery and age. The primary cause of underactivity is increased connective tissue in relation to detrusor muscle; however, detrusor myocyte function remains normal. Finally, the increase of the smooth muscle content in the paediatric bladder group indicates a remodelling response of the bladder to surgical correction and time. Excess gestational fibrosis is associated with changed expression of key proteins in the Wnt -signalling pathway, a potential aetiological factor and therapeutic target. Conclusion: Results point to connective tissue deposition as the primary pathological process that determines bladder function with normal myocyte function. Future research that reduces connective tissue deposition may lead to improvement in outcomes for these children.Image 1